Factors Influencing E-Entrepreneurial Intention among Female Students in Saudi Arabia - Alzamel, Samar; Nazri, Mohammad; Omar, Safiah (International Journal of Criminology and Sociology, 2022)
Entrepreneurship has attracted enhanced attention in the twenty-first century. Entrepreneurial schemes vary the production and service sectors of a country's economy and lead it to increase its revenues and materialize speedy growth and development. However, the current Saudi regime has allowed enhanced social space to females, and a new social environment has paved the way for them to partake business opportunities actively. Thus, the aim of this study is to explore the direct impact of perceived social support towards e-entrepreneurial intention as well as the direct influence of perceived social support on the theory of planned behavior (TPB) components encompass attitude towards entrepreneurial, subjective norms, and self-efficacy of entrepreneurship. Also, this study examines the direct effect of the theory of planned behavior (TPB) components (attitude towards entrepreneurial, subjective norms, and entrepreneurial self-efficacy). Data were collected through questionnaires which were completed by 534 undergraduate female Saudi students have been selected randomly studying at various Saudi universities. Structural Equation Modeling (SEM) was used to test the model, and data analysis was carried out using Structural Equation Modelling – Partial Least Square (SEM-PLS). This study, therefore revealed that perceived social support has a positive impact on the e-entrepreneurship intention as well as the relationship between perceived social support and the components of the TPB (attitude towards entrepreneurial intention, subjective norms, and entrepreneurial self-efficacy) were statistically significant. Subsequently, the direct effect of the TPB components (attitude towards entrepreneurial and entrepreneurial self-efficacy) was significant, while the direct effect related to subjective norms and the e-entrepreneurial intention was insignificant. Therefore, this study offers theoretical and practical contributions to entrepreneurial studies.